Augmentation of the Ulnar Motor Nerve Repair with Anterior Interosseous Nerve in High Ulnar Nerve Palsy: Our Clinical Experience - Gopika Jith; Kaushik Mahadik; Santanu Suba; Sanjay Kumar Giri (Indian Journal of Plastic Surgery)
Following proximal ulnar nerve repair, there will be a delay in innervating the distally placed intrinsic muscles of the hand, which can lead to irreversible damage to the intrinsic motor end plates. Supercharging with end-to-side anterior interosseous nerve (AIN) transfer can augment the results of nerve repair by babysitting the motor end plates and thus preventing its denervation. Recently, there have been discussions regarding whether AIN, which contains only 500 axons, can augment the ulnar motor branch, which contains approximately 1,500 axons. In one of our cases, electromyogram following surgery showed activity in the first dorsal interossei and abductor digiti minimi without any signs of reinnervation in the flexor carpi ulnaris. This may support the contribution of AIN in supplying the intrinsic muscles. Considering the low morbidity of the procedure and potential improvements in muscle strength, all patients undergoing ulnar nerve repair in high ulnar nerve palsies can be counseled to undergo an end-to-side AIN transfer.